Analysis of shoreline changes on the northeast coast of Nunukan Island, Nunukan Regency, North Kalimantan Province - Andi Ummung; Wahyuti Wahyuti; Jaya Jaya (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
This study aimed to analyze changes in the coastline in the Northeast of Nunukan Island, North Kalimantan Province and to determine the area in the Northeast of Nunukan Island, North Kalimantan Province, which experienced changes in the coastline. This research was conducted in February - March 2022 on the Northeast Coast of Nunukan Island, North Kalimantan Province. The type of data collected is satellite imagery for the last 6 years, 2017-2022. Data were analyzed using GIS software with cropping, radiometric correction, geometric correction, image enhancement, shoreline digitization and overlay methods. The results showed that the rate of change of the eastern coastline of Nunukan Island in 2017 was 13,457.91 m long, 2018 was 14,266.82 m long, 2019 was 14,787.25 m long, 2020 was 14,762.21 m long, 2021 was 15,369.23 m long, and in 2022 it is 15,968.22 m. The area that has experienced a change in coastline on Nunukan Island, North Kalimantan Province, namely in 2017 covering an area of 21.70 ha, in 2018 covering an area of 22.27 ha, in 2019 covering an area of 23.34 ha, in 2020 covering an area of 23.74 ha, in 2021 covering an area of 24 .26 ha and in 2022 it will be 32.82 ha. This study concludes that the area of change in the coastline has changed significantly from 2017 to 2022.